Survival and Clinicopathological Significance of SIRT1 Expression in Cancers: A Meta-Analysis - Sun, Min; Du, Mengyu; Zhang, Wenhua; Xiong, Sisi; Gong, Xingrui; Lei, Peijie; Zha, Jin; Zhu, Hongrui; Li, Heng; Huang, Dong; Gu, Xinsheng (Frontiers in Endocrinology, 2019)
Background: Silent information regulator 2 homolog 1 (SIRT1) is an evolutionarily conserved enzymes with nicotinamide adenine dinucleotide (NAD)+-dependent deacetylase activity. SIRT1 is involved in a large variety of cellular processes, such as genomic stability, energy metabolism, senescence, gene transcription, and oxidative stress. SIRT1 has long been recognized as both a tumor promoter and tumor suppressor. Its prognostic role in cancers remains controversial. Methods: A meta-analysis of 13,138 subjects in 63 articles from PubMed, EMBASE, and Cochrane Library was performed to evaluate survival and clinicopathological significance of SIRT1 expression in various cancers. Results: The pooled results of meta-analysis showed that elevated expression of SIRT1 implies a poor overall survival (OS) of cancer patients [Hazard Ratio (HR) = 1.566, 95% CI: 1.293–1.895, P < 0.0001], disease free survival (DFS) (HR = 1.631, 95% CI: 1.250–2.130, P = 0.0003), event free survival (EFS) (HR = 2.534, 95% CI: 1.602–4.009, P = 0.0001), and progress-free survival (PFS) (HR = 3.325 95% CI: 2.762–4.003, P < 0.0001). Elevated SIRT1 level was associated with tumor stage [Relative Risk (RR) = 1.299, 95% CI: 1.114–1.514, P = 0.0008], lymph node metastasis (RR = 1.172, 95% CI: 1.010–1.360, P = 0.0363), and distant metastasis (RR = 1.562, 95% CI: 1.022–2.387, P = 0.0392). Meta-regression and subgroup analysis revealed that ethnic background has influence on the role of SIRT1 expression in predicting survival and clinicopathological characteristics of cancers. Overexpression of SIRT1 predicted a worse OS and higher TNM stage and lymphatic metastasis in Asian population especially in China. Conclusion: Our data suggested that elevated expression of SIRT1 predicted a poor OS, DFS, EFS, PFS, but not for recurrence-free survival (RFS) and cancer-specific survival (CCS). SIRT1 overexpression was associated with higher tumor stage, lymph node metastasis, and distant metastasis. SIRT1-mediated molecular events and biological processes could be an underlying mechanism for metastasis and SIRT1 is a therapeutic target for inhibiting metastasis, leading to good prognosis.